Education for Global Citizenship in Times of Crisis (Comillas Journal of International Relations, 2020)
The current crisis of COVID-19 is posing a serious obstacle to the fulfilment of the 2030 Agenda, with the forecast of an increase in the world poverty rate, reversing many of the achievements made in recent years. Likewise, the pandemic is leading to a decline in access to the right to quality education and an increase in the inequalities of opportunities generated by the digital divide, affecting millions of students who have stopped going to school. However, despite all the threats aroused by the current context, the opportunities that are emerging in this crisis are glimpsed. Compliance with the SDGs is undoubtedly a fundamental strategy to face it and, in this sense, education for global citizenship is a key tool to accompany processes that promote the construction of an active, critical and generator of social change citizenship.
Keywords: Global Citizenship Education; education rights; 2030 Agenda; Sustainable Development Goals; SDGs; crisis; COVID-19; agents of social transformation